2019
DOI: 10.1093/geroni/igy038
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Technology for Cognitive Assessment of Older Adults: A Scoping Review

Abstract: Background and ObjectivesThe number of people diagnosed with dementia is rising appreciably as the population ages. In an effort to improve outcomes, many have called for facilitating early detection of cognitive decline. Increased use of mobile technology by older adults provides the opportunity to deliver convenient, cost-effective assessments for earlier detection of cognitive impairment. This article presents a review of the literature on how mobile platforms—smartphones and tablets—are being used for cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
125
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(144 citation statements)
references
References 58 publications
2
125
0
1
Order By: Relevance
“…These findings confirm recent suggestions that video games incorporate elements and cognitive challenges shared with psychological tasks (Holmgard et al, 2016). Furthermore, results indicate that game-based measures of cognitive and motor performance can be used to assess and monitor cognitive function in normal aging and neurodegenerative diseases (Koo and Vizer, 2019;Mandryk and Birk, 2019). Significant correlations between NL-based time and movement performance with tests of psychomotor, attentional, visuoconstructional, and executive functions support our assumption that NL puzzles share cognitive components with classical maze tasks (Snellgrove, 2005;Kirsch et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings confirm recent suggestions that video games incorporate elements and cognitive challenges shared with psychological tasks (Holmgard et al, 2016). Furthermore, results indicate that game-based measures of cognitive and motor performance can be used to assess and monitor cognitive function in normal aging and neurodegenerative diseases (Koo and Vizer, 2019;Mandryk and Birk, 2019). Significant correlations between NL-based time and movement performance with tests of psychomotor, attentional, visuoconstructional, and executive functions support our assumption that NL puzzles share cognitive components with classical maze tasks (Snellgrove, 2005;Kirsch et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…A novel approach to address these issues is the use of video games to study age and neurodegenerative diseaserelated differences in cognitive function (Boot, 2015;Koo and Vizer, 2019). Video games involve solving cognitive challenges that require a range of cognitive abilities and often share properties with psychological tests (Holmgard et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, our pattern of mean RT across the lifespan, which peaks in the early 20s, replicates gold standard longitudinal work (e.g., Deary and Der, 2005), as we have previously shown that lifespan patterns of change in processing speed replicate work from these gold standard studies (Hartshorne and Germine, 2015). Given the utility and ease of web-based cognitive tests [see Koo and Vizer (2019) for a recent review], an approach that integrates multiple metrics may be useful for clinicians and researchers to study cognitive performance and performance variation at many stages across the lifespan.…”
Section: Discussionsupporting
confidence: 77%
“…Multilevel model results for Symbol Search, Dot Memory, and Card Matching Note. Results are from 47 women assessed up to five times a day (prompt; 1-5) across the 2-week assessment period (days in study:[1][2][3][4][5][6][7][8][9][10][11][12][13][14]. EMA patient reported outcomes reflect differences between breast cancer patients (person mean) and within-person variation (daily fluctuation).Abbreviation: EMA, ecological momentary assessment.…”
mentioning
confidence: 99%